Health and well-being in the imagination of the latin american population 2019 - 2020 - Hernández-Garnica , Clotilde; Suárez-Lugo, Nery de la Concepcion (Horizonte Sanitario, 2022)
Objectives: To characterize social representations of Latin-American population about health life, health and wellbeing establish similitudes, differences and discrepancies between what people consider health and the concept of the OMS and the OPS.Materials and methods: Descriptive study, transversal, multicenter (Colombia, Cuba, Mexico, Panama and Peru) employing bibliographic, documentary, survey and expert consultation using the modified Delphi method. Universe Population from 18 to 80 years old, non probabilistic sampling, convenience criteria. Sampling 1327 subjects: Colombia (103), Cuba (80), Mexico (1010), Panama (84) and Peru (50). Were explored sociodemographic variables, healthy life, health, wellbeing and activities autoconcept that generate and produce health and wellbeing. Data was processed in the statistic package SPSS 20 to perform descriptive statistic (central tendency and correlation).Results: The population relates the concept of health with absence of illness and illness with loss of health, not with behaviors that can generate or damage it life styles. The social representation of wellbeing gives the most important to the health services access. There is no clear differentiation between the social health and wellbeing representation.Conclusions: The population does not perceive itself as an active subject and transformer in the activities that generate a healthy life. The universal health underlays in the social representation of wellbeing when showing the importance population concedes to the access to health services. The concept of health promoted by the OMS is something not interiorized by Latin American countries.Keywords: Health; Wellbeing; Healthy; Representations; Autoconcept